2018
DOI: 10.3389/fmicb.2018.00848
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma Biofertilizer Links to Altered Soil Chemistry, Altered Microbial Communities, and Improved Grassland Biomass

Abstract: In grasslands, forage and livestock production results in soil nutrient deficits as grasslands typically receive no nutrient inputs, leading to a loss of grassland biomass. The application of mature compost has been shown to effectively increase grassland nutrient availability. However, research on fertilization regime influence and potential microbial ecological regulation mechanisms are rarely conducted in grassland soil. We conducted a two-year experiment in meadow steppe grasslands, focusing on above- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 63 publications
4
48
0
2
Order By: Relevance
“…The results of the alpha and beta diversity analyses showed that Trichoderma spp. inoculation had a significant effect on the community structure of fungi in the rhizosphere soil of seedlings; this is consistent with the research results of Yu [73], Shen [60], Zhang [30]. Trichoderma spp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the alpha and beta diversity analyses showed that Trichoderma spp. inoculation had a significant effect on the community structure of fungi in the rhizosphere soil of seedlings; this is consistent with the research results of Yu [73], Shen [60], Zhang [30]. Trichoderma spp.…”
Section: Discussionsupporting
confidence: 91%
“…mongolica. The growth of seedlings inoculated with E15 was significantly higher than that of seedlings inoculated with ZT05, and the growth and structure of seedling roots inoculated with ZT05 was higher than that of seedling roots inoculated with E15.Many reports have shown that Trichoderma inoculation has significant promotion effects on plants seedlings and crops yields, such as those of cotton [54], tomato [55], and Leymus chinensis [8,30]. Harman [7] showed that the inoculation of Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma spp. are proposed as major plant growth-promoting fungi in soils, signi cantly alter the rhizosphere soil chemistry, regulate microbial communities and improve grassland biomass [34]. Trichoderma species were frequently isolated from external mycelial cortices by culturedependent approach, and also have been identi ed by high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fungi, the BF treatments increased the abundance of Trichoderma, Metarhizium, and Mortierella. Trichoderma are plant growth-promoting fungi that enhance plant nutrient uptake, production of growth hormones, and protect plants from pathogen infection [41].…”
Section: Discussionmentioning
confidence: 99%